Fostering Social Entrepreneurship from the Classroom: The Role of Entrepreneurial Attitude as a Mediator of Entrepreneurship Education - Kurjono Kurjono; Sulthan Yusuf; Ali Usman (Universitas Negeri Padang, 2025)
This study aims to examine the effect of entrepreneurship education on social entrepreneurship intention, with entrepreneurial attitude as a mediating variable, among vocational high school students in Cirebon City, Indonesia. The population of this study consisted of vocational high school students in Cirebon City, and a simple random sampling technique was used to obtain 195 respondents. Data were collected using a questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the relationships among entrepreneurship education, entrepreneurial attitude, and social entrepreneurship intention. The results indicate that entrepreneurship education has a positive effect on social entrepreneurship intention (H1), entrepreneurial attitude positively influences social entrepreneurship intention (H2), and entrepreneurship education has a positive impact on entrepreneurial attitude (H3). Furthermore, entrepreneurial attitude partially mediates the relationship between entrepreneurship education and social entrepreneurship intention. This study contributes to the literature by highlighting the mediating role of entrepreneurial attitude in linking entrepreneurship education to social entrepreneurship intention among vocational high school students, particularly in the context of social entrepreneurship. Practically, the findings suggest the importance of integrating social entrepreneurship values into vocational high school entrepreneurship curricula, along with implementing applied learning programs such as internships and entrepreneurship incubators to strengthen students’ social entrepreneurial attitudes.